ChemInform Abstract: Palladium Catalyzed β‐Selective Oxidative Heck Reaction of an Electron‐Rich Olefin. Issue 19 (13th May 2014) - Meng, Lingkui; Liu, Chao; Zhang, Wei; Zhou, Chao; Lei, Aiwen
Abstract The reaction proceeds under mild conditions and does not require any ligand or base.